Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Thanks to whoever decides to help

Thanks To Whoever Decides To Help class=

Sagot :

[tex]\displaystyle\ S=Vt=> V=\frac{S}{t }[/tex]        in our case, S is d(h) ; and t is t (x), then                      [tex]\displaystyle\ V=\frac{d(x)}{t(h)}=\bigg(\frac{d}{t} \bigg )(h)=\frac{6h^2-h-1}{2h-1} =\frac{2h^2-h+4h^2-1}{2h-1} =\\\\\\\\\frac{h\underline{(2h-1)}+\underline{(2h-1)}(2h+1)}{2h-1} =\frac{(3h+1)(2h-1)}{2h-1} =\boxed{3h+1}\\\\\\Answer: \boxed{V=3h+1}[/tex]                                      

Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.